Training general practitioners in the ABC versus 5As method of delivering stop-smoking advice: a pragmatic, two-arm cluster randomised controlled trial. Issue 3 (26th July 2021) - Kastaun, Sabrina; Leve, Verena; Hildebrandt, Jaqueline; Funke, Christian; Klosterhalfen, Stephanie; Lubisch, Diana; Reddemann, Olaf; McRobbie, Hayden; Raupach, Tobias; West, Robert; Wilm, Stefan; Viechtbauer, Wolfgang; et al.
This study assessed the effectiveness of a 3.5-h training session for general practitioners (GPs) in providing brief stop-smoking advice and compared two methods of giving advice – ABC versus 5As – on the rates of delivery of such advice and of recommendations of evidence-based smoking cessation treatment during routine consultations. A pragmatic, two-arm cluster randomised controlled trial was carried out including a pre-/post-design for the analyses of the primary outcome in 52 GP practices in Germany. Practices were randomised (1:1) to receive a 3.5-h training session (ABC or 5As). In total, 1937 tobacco-smoking patients, who consulted trained GPs in these practices in the 6 weeks prior to or following the training, were included. The primary outcome was patient-reported rates of GP-delivered stop-smoking advice prior to and following the training, irrespective of the training method. Secondary outcomes were patient-reported receipt of recommendation/prescription of behavioural therapy, pharmacotherapy or combination therapy for smoking cessation, and the effectiveness of ABC versus 5As regarding all outcomes. GP-delivered stop-smoking advice increased from 13.1% (n=136 out of 1039) to 33.1% (n=297 out of 898) following the training (adjusted odds ratio (aOR) 3.25, 95% CI 2.34–4.51). Recommendation/prescription rates of evidence-based treatments were low (<2%) pre-training, but had all increased after training ( e.g. behavioural support: aOR 7.15, 95% CI 4.02–12.74). Delivery of stop-smoking advice increased non-significantly (p=0.08) stronger in the ABC versus 5As group (aOR 1.71, 95% CI 0.94–3.12). A single training session in stop-smoking advice was associated with a three-fold increase in rates of advice giving and a seven-fold increase in offer of support. The ABC method may lead to higher rates of GP-delivered advice during routine consultations. A brief, single training session is effective in changing GP behaviour for providing stop-smoking advice and evidence-based cessation treatment. Training according to the very brief ABC method may lead to higher rates of such GP-delivered advice. https://bit.ly/2TciPSO